β-glucosidase from thermophilic fungus Thermoascus crustaceus: Production and industrial potential - Garbin, Andreza P.; Garcia, Nayara F.L.; Cavalheiro, Gabriela F.; Silvestre, Maria Alice; Rodrigues, André [UNESP]; DA PAZ, Marcelo F.; Fonseca, Gustavo G.; Leite, Rodrigo S. R. (FapUNIFESP (SciELO), 2021)
Microbial β-glucosidases can be used in several industrial processes, including production of biofuels, functional foods, juices, and beverages. In the present work, production of β-glucosidase by solid state cultivation of the fungus Thermoascus crustaceus in a low-cost cultivation medium (comprising agroindustrial residues) was evaluated. The highest production of β-glucosidase, about 415.1 U/g substrate (or 41.51 U/mL), was obtained by cultivating the fungus in wheat bran with 70% humidity, during 96 h at 40°C. The enzymatic activity was optimum at pH 4.5 and 65°C. β-Glucosidase maintained its catalytic activity when incubated at a pH range of 4.0-8.0 and temperature of 30-55°C. The enzyme was strongly inhibited by glucose; even when the substrate and glucose concentrations were equal, the inhibition was not reversed, suggesting a non-competitive inhibition. In the presence of up to 10% ethanol, β-glucosidase maintained its catalytic activity. In addition to β-glucosidase, the enzymatic extract showed activity of 36 U/g for endoglucanase, 256.2 U/g for xylanase, and 18.2 U/g for β-xylosidase. The results allow to conclude that the fungus T. crustaceus has considerable potential for production of β-glucosidase and xylanase when cultivated in agroindustrial residues, thereby reducing the cost of these biocatalysts.
Keywords: Cellulases; Filamentous fungus; Industrial enzymes; Solid state cultivation; Xylanases